Frequency of Treatment of Foot Wounds in Diabetes Melitus Patients Infected with Covid -19 - Astuti, Sri Lestari Dwi; Suyanto, Suyanto; Rohimah, Yeni Tutu; Insiyah, Insiyah (Poltekkes Kemenkes Surakarta, 2023)
Background: Frequency of Treatment of Foot Wounds in Diabetes Melitus Patients Infected with Covid -19 Objective: to assess the differences in the frequency of treatment in patients with or without arterial injuries. Purpose to assess the differences in the frequency of treatment in patients with or without arterial injuries. Methods: This type of quantitave research was comparative and descriptive to assess the difference in the frequency of treatment between those with arterial injuries and those without arterial injuries. A sample of 60 people who had been exposed to COVID-19 and had diabetic foot wounds was split into two groups: 35 people who had arterial injuries and 25 people who did not. Samples were taken using purposive sampling method Both groups of respondents recorded the frequency of wound care that had been received and analyzed it using the Chi- square test with an error degree of 0.05. Results: Patients exposed to Covid 19 showed a difference in the frequency of treating diabetic foot wounds between those who had vascular injuries and those who did not, with a P value of 0.049 0.05 and an OR of 95% CI = 2.114. Conclusion: There is a difference in the frequency of wound care for DM patients between those exposed to COVID-19 and experiencing arterial injuries and those who do not have arterial injuries. Patients who experience arterial injuries have the risk of increasing the frequency of wound care by 1.114 times compared to those who do not experience arterial injuries.